Distributive leadership roles for primary school teachers’ efficiency in new norm: focus group analysis - Rumeli, Muaza Shifa; Md Rami, Ahmad Aizuddin; Abdul Wahat, Nor Wahiza; Samsudin, Shamsulariffin (UiTM Press, 2022)
As a result of the COVID-19 pandemic, the education sector in Malaysia had undergone drastic changes and new norms are now in place. Among them are online home teaching and learning (PdPR) activities. This situation has become challenging and worrying especially in the primary school education sector. The Ministry of Education (2021) reported that there were 2,741,837 pupils in primary schools, compared to 2,037,433 pupils in secondary schools. These large numbers certainly affect the way school leaders manage the available resources. To alleviate this problem, school leaders are seen to have played an important role in helping teachers and pupils to adapt to the new online home teaching and learning (PdPR) environment. Therefore, this study examines the distributive leadership practices on the efficiency of primary school teachers during the COVID-19 pandemic period and challenges from the perspective of school leaders in managing and leading schools during this difficult period. A qualitative design with a phenomenology approach was used in studying and exploring their experiences. Five informants had collaborated in this study, and five main themes emerged: designation and sharing of school missions, visions, and goals; sharing of responsibilities; giving positive changes to teachers and students; giving changes to teachers to develop leadership skills; and cooperation - coordination and mutual understanding between education leaders and teachers. Through these themes, it is found that distributive leadership can be consistently pre-dedicated across all educational institutions. Besides sharing responsibilities, distributive leadership had enhanced teachers' knowledge and skills.